Evaluation of innovative strategy in an industrial enterprise. (Economics and region, 2017)
UDC 339.137.2:658.0 Hanna Kozachenko, D.Sc. (Economics), professor. Poltava National Technical Yuri Kondratyuk University. Yevhen Shapran, D.Sc. (Technical Sciences), professor. National technical University «Kharkiv Polytechnical Institute». Evaluation of innovative strategy in an industrial enterprise. There are criteria of evaluating novelties suggested in the article (measure of readiness to usage, level of significance, scale of impact on the enterprise activity, level of risk). Common scheme of evaluating strategy of innovations at the enterprise and indicators of such evaluating (level of progressiveness, level of risk, and level of actuality) are considered. Kinds of risk for the strategy of innovations of the enterprise and potential methods of its compensation are considered. Kinds of strategy of innovations at the enterprise (attack, defensive, leading and innovational) are suggested. It is shown that every kind of strategy of innovations should correspond with using competitive strategy of the enterprise (violent, patient, explerent or commutant). Keywords: enterprise, innovation, strategy of innovations, evaluating, indicators, criteria.